(untitled) (Estudos em Design, 2020)
Editores Cristina Portugal Rita Maria de Souza Couto Avaliadores desta edição v. 28, n. 1 (2020) Aline Eyng Savi Alexandre Santos de Oliveira Álvaro José Barbosa Sousa Ana Veronica Pazmino Andrea de Souza Almeida Antonio Ferreira Colchete Filho Beany Monteiro] Berenice Santos Gonçalves Claudio Henrique da Silva Cristina Portugal Cyntia Santos Malaguti Daniel Lourenço Daniel Raposo Doris Kosminsky Eloiza Andrade Corrêa Fernanda de Abreu Cardoso Fernanda Martins Frederico Braida Gabriel Patrocínio Haroldo Gallo Hugo Cristo Helena Rugai Bastos Ione Maria Ghislene Bentz Joao Eduardo chagas Sobral Leticia Affini Letícia Pedruzzi Fonseca Luiz Agner Luiza Novaes Marcos Beccari Marcos Braga Mariano Lopes de Andrade Neto Marizilda Menezes Rafaella Peres Raimundo Lopes Diniz Ranielder Fábio de Freitas Renata Amorim Cadena Rosimeri Franck Pichler Sandra Souza Tiago Barros Pontes Silva Verônica Freire Virginia Tiradentes Souto Washington Dias Lessa